A comparative analysis of renewable energy financing models in Brazil, China, India and South Africa - Kamara, Rivhatshinyi Nicole (My University, 2016)
This thesis reviewed research papers, reports, conference documents and policy documents that looked at financial models used to finance RE projects in Brazil, China, India and South Africa.The comparison between the financing models revealed the following; Both Brazil and China’s financing model is a centralised government led model which might not necessarily work in the South African context. The India decentralised model is similar to the South African model, with the exception that corporate finance is widely used in India and Project Finance in South Africa. Thus there are lessons to be learnt from each country, however no single country financing model was found to be suitable for South Africa. Accordingly, this paper therefore recommends that South Africa’s model be altered to incorporate project bonds. The use of these bonds in the current financial model will ensure that banks are able to lend to projects on short term basis; thus, managing their liquidity and their asset--liability effectively. Further, some institutional investors have shown an interest in funding projects at the construction stage, and the inclusion of project bonds would ensure that more of these investors play a role in financing projects. Key Words GDP-Gross Domestic Product; GW- Gigawatts; DoE-Department of Energy; REIPPPP- Renewable Energy Independent Power Producer Procurement Programme; BEE-Black Economic Empowerment; RE-Renewable Energy; SSA-Sub Saharan Africa; PPA-Power Purchase Agreement; FIT-Feed In Tariff; DFIDevelopment Finance Institution; MDB-Multilateral Development Bank
Thesis submitted in fulfilment of the requirements for the degree of Master of Management in Finance & Investment in the Faculty of Commerce Law and Management Wits Business School, Johannesburg 2016
Keywords: Energy industries--Finance; Renewable energy sources